The Relationship between Test Anxiety, Epistemological Beliefs and Problem Solving among Students - Vali Mehdinezhad; Zeinab Bamari (Springer, 2015)
The purpose of this study was to investigate the test anxiety, epistemological beliefs and problem solving among students. The target population of the current research was all the students of University of Sistan and Baluchestan in the academic year 2013-2014 and the number of the sample was 375. They were selected using a classified and simple random method. The main tools to collect data were three questionnaires. The test anxiety questionnaire by Abolqasemi et al. (1996), epistemological beliefs questionnaire by Schommer (1998), and Patio problem-solving questionnaire (2002) were used. The reliability of these questionnaires was calculated through Cronbach's Alpha test as 0.93, 0.75 and 0.88. To test the research questions, single sample t-test, independent t and Pearson correlative coefficient were adopted using SPSS software, version 20. The results showed that students have relatively high-test anxiety. It was also shown that they have relatively good epistemological beliefs. The students' status to solve the problems is also satisfactory to some extent. There is a positive and significant relationship between test anxiety and epistemological beliefs at low level. But no statistically meaningful relationship was noticed between test anxiety and problem solving. Meanwhile the results showed that there is a negative and meaningful relationship at low level between epistemological beliefs and problem solving.